Waste from baking soda production to be used for biocementation - Kovshar, Iryna; Stabnikov, Victor (My University, 2024)
The current cost of the biocementation process prevents its widespread use in civil and geotechnical engineering. The use of industrial waste as raw materials for biocementation not only diminishes the cost of biocement, but also reduces the load on the environment, thereby contributing to its conservation. In baking soda production, for instance, calcium chloride (CaCl2) is generated as a byproduct. Meanwhile, this compound is one of the necessary components for the production of biocement. Поточна вартість процесу біоцементації перешкоджає його широкому використанню в цивільному та геотехнічному будівництві. Використання промислових відходів як сировини для біоцементації не тільки знижує вартість біоцементу, але й зменшує навантаження на навколишнє середовище, тим самим сприяючи його збереженню. Наприклад, у виробництві харчової соди хлорид кальцію (CaCl2) утворюється як побічний продукт. Тим часом ця сполука є одним із необхідних компонентів для виробництва біоцементу.
Keywords: soda; biocementation; біоцементація; уреаза; кафедра біотехнології і мікробіології